Respuesta :
There are a lot of choices for the two numbers; this is because no other condition has been placed on the numbers to pinpoint the exact numbers required.
x = 1st number
y = 2nd number
The equation would be:
4(x+y) = 172
4(x+y)/4 = 172/4
x + y = 43
If we get the value of x. then, x = 43 - y
Substitute x by its value
43 -y + y = 43
43 = 43
y = 0
If y = 0 then x = 43 to get the sum of 43
x y x + y 4x 4y 4x + 4y
43 0 43 172 - 172
42 1 43 168 4 172
41 2 43 164 8 172
40 3 43 160 12 172
39 4 43 156 16 172
38 5 43 152 20 172
37 6 43 148 24 172
36 7 43 144 28 172
35 8 43 140 32 172
34 9 43 136 36 172
33 10 43 132 40 172
32 11 43 128 44 172
31 12 43 124 48 172
30 13 43 120 52 172
29 14 43 116 56 172
28 15 43 112 60 172
27 16 43 108 64 172
26 17 43 104 68 172
25 18 43 100 72 172
24 19 43 96 76 172
23 20 43 92 80 172
22 21 43 88 84 172
x = 1st number
y = 2nd number
The equation would be:
4(x+y) = 172
4(x+y)/4 = 172/4
x + y = 43
If we get the value of x. then, x = 43 - y
Substitute x by its value
43 -y + y = 43
43 = 43
y = 0
If y = 0 then x = 43 to get the sum of 43
x y x + y 4x 4y 4x + 4y
43 0 43 172 - 172
42 1 43 168 4 172
41 2 43 164 8 172
40 3 43 160 12 172
39 4 43 156 16 172
38 5 43 152 20 172
37 6 43 148 24 172
36 7 43 144 28 172
35 8 43 140 32 172
34 9 43 136 36 172
33 10 43 132 40 172
32 11 43 128 44 172
31 12 43 124 48 172
30 13 43 120 52 172
29 14 43 116 56 172
28 15 43 112 60 172
27 16 43 108 64 172
26 17 43 104 68 172
25 18 43 100 72 172
24 19 43 96 76 172
23 20 43 92 80 172
22 21 43 88 84 172